Territory Quality Predicts Avian Vocal Performance Across an Urban-Rural Gradient - Phillips, Jennifer N.; Cooper, W. Justin; Luther, David A.; Derryberry, Elizabeth P. (Frontiers in Ecology and Evolution, 2020)
Human activity around the globe is a growing source of selection pressure on animal behavior and communication systems. Some animals can modify their vocalizations to avoid masking from anthropogenic noise. However, such modifications can also affect the salience of these vocalizations in functional contexts such as competition and mate choice. Such is the case in the well-studied Nuttall’s white-crowned sparrow (Zonotrichia leucophrys nuttalli), which lives year-round in both urban San Francisco and nearby rural Point Reyes. A performance feature of this species' song is salient in territorial defense, such that higher performance songs elicit stronger responses in simulated territorial intrusions; but songs with lower performance values transmit better in anthropogenic noise. A key question then is whether vocal performance signals male quality and ability to obtain high quality territories in urban populations. We predict white-crowned sparrows with higher vocal performance will be in better condition and will tend to hold territories with lower noise levels and more species-preferred landscape features. Because white-crowned sparrows are adapted to coastal scrub habitats, we expect high quality territories to contain lower and less dense canopies, less drought, more greenness, and more flat open ground for foraging. To test our predictions, recorded songs and measured vocal performance and body condition (scaled mass index and fat score) for a set of urban and rural birds (N = 93), as well as ambient noise levels on their territories. Remote sensing metrics measured landscape features of territories, such as drought stress (NDWI), greenness (NDVI), mean canopy height, maximum height, leaf area density (understory and canopy), slope, and percent bare ground for a 50m radius on each male territory. We did not find a correlation between body condition and performance but did find a relationship between noise levels and performance. Further, high performers held territories with lower canopies and less dense vegetation, which are species-preferred landscape features. These findings link together fundamental aspects of sexual selection in that habitat quality and the quality of sexually selected signals appear to be associated: males that have the highest performing songs are defending territories of the highest quality.